Anesthetic Effect of the Fascia Iliaca Compartment Block with Different Approaches on Total Hip Arthroplasty and Its Effect on Postoperative Cognitive Dysfunction and Inflammation - Feng, Tengchen; Zhao, Jibo; Wang, Jiayi; Sun, Xiaojia; Jia, Tong; Li, Fulong (Frontiers in Surgery, 2022)
Objective Comparison of anesthesia effects of inside and outside fascia iliaca compartment block (FICB) in total hip arthroplasty (THA), and to study the effect of different approaches of FICB on postoperative cognitive dysfunction (POCD) and serum inflammatory cytokines in THA patients. Methods 60 cases patients who received THA treatment from January 2021 to December 2021 were divided into Inside group (Inside approach FICB) and Outside group (outside approach FICB) according to different approaches of FICB. 48 hours after surgey, we comapred the use of ropacaine dosage, visual analogu scale (VAS) score, the use of patientcontrolled analgesia (PCA), mini-mental state examination (MMSE) score, the incidence of POCD and the serum levels of IL-1, IL-6. Secondary indicators include surgical indicators and the quality of anesthesia cannula. Results The ratio of Re-fix the catheter, intubation time, and the use of ropacaine dosage at 48 hours after surgey in Outside group were significantly higher than that in Inside group (P<0.05), while the depth of cannulation in Outside group was significantly lower than that in Inside group (P<0.05). VAS scores were comparable between Inside group and Outside group except at 24 hours after surgery. The use of PCA from 24 hours to 48 hours after surgery in Outside group is significantly higher than that in Inside group (P<0.05). The MMSE score and the incidence of POCD in Outside group are higher than that in Inside group. At the same time, the serum IL-1beta levels at 1 and 6 hours after surgery and the serum IL-6 levels at 1, 6, 24 and 48 hours after surgery in Outside group are significantly higher than that in Inside group (P<0.05). Conclusion The inside approach FICB has better anesthesia effect and postoperative analgesia than outside approach FICB on THA treatment, and the amounts of analgesic drugs used after surgery, the incidence of POCD and serum cytokine levels are lower.